Study on Complexity Planning Model of Pumped Storage in Abandoned Open-Pit Mine: A Case Study of Fushun Open-Pit Mine - Luo, Pingjia; Han, Xueqi; Chen, Ning (Frontiers in Earth Science, 2022)
Open pit mining is one of the main exploiting methods for solid mineral resources. After more than one hundred years of high-intensity development, there are a large number of abandoned open pit mines and related mining relics in the world. The reconstruction of Pumped Hydraulic Energy Storage system (PHES) from abandoned open pit mine is an effective utilization mode of the abandoned underground space in recent years. The project planning of PHES should consider not only the technical and economic feasibility of PHES power station, but also a series of problems, such as comprehensive utilization of mine dump, slope treatment, industrial heritage and cultural inheritance, ecological environment restoration of mining area, transformation and matching of nearby resource exhausted cities. This constitutes a complex planning problem of pumped storage in abandoned open-pit mine. This paper takes Fushun open pit mine, the second largest open pit mine in the world, as the analysis object, and abstracts a variety of application modes of pumped storage in abandoned open pit mine with the model research method. On this basis, the modes abstracted such as the single pit oil-water co-storage mode, single pit gravity dam reinforcement mode, multi pit linkage energy storage mode, multi pit and dump linkage energy storage mode are all carefully studied in this paper. A series of supporting integrated program are proposed for each mode with regard to ecological restoration, multi-energy complementary, cultural tourism governance, etc. In addition, based on the PHES with abandoned open-pit mine, this paper also explores the sustainable development of resource exhausted cities and the transmission of their core industries.